Role of 532 nm transfoveal subthreshold micropulse laser in non-resolving central serous chorioretinopathy with subfoveal leaks - Ambiya, Vikas (Ther Adv Ophthalmol, 2020)
PURPOSE: The purpose of this study was to evaluate the role of 532 nm transfoveal subthreshold micropulse laser in non-resolving central serous chorioretinopathy with subfoveal leak. METHODS: A retrospective chart analysis of 23 eyes of 21 patients with central serous chorioretinopathy was performed. Inclusion criteria include vision loss ⩾3 months and focal subfoveal leak on fluorescein angiography. Exclusion criteria include prior treatment for central serous chorioretinopathy and chronic central serous chorioretinopathy. All eyes were treated with 532 nm subthreshold micropulse laser (5% duty cycle). Visual acuity score, contrast sensitivity, autofluorescence, spectral domain optical coherence tomography, and fundus fluorescein angiography were assessed at baseline, 1, 3, 6 months. RESULTS: Average visual acuity score (letters) improved from 66.0 ± 8.51 (baseline) to 71.35 ± 8.48 (1 month, p < 0.01), 77.30 ± 11.34 (3 months, p < 0.01), 80.17 ± 9.30 (6 months, p < 0.01). Contrast sensitivity improved from 0.75 ± 0.30 to 1.30 ± 0.37 (p < 0.01) at 6 months. Two eyes needed rescue laser at 3 months followed by photodynamic therapy at 6 months; two eyes needed rescue laser at 6 months. CONCLUSION: The 532 nm subthreshold micropulse laser is safe in non-resolving central serous chorioretinopathy with subfoveal leaks.